Genome-Wide Association Studies in Indian Buffalo Revealed Genomic Regions for Lactation and Fertility - Vohra, Vikas; Chhotaray, Supriya; Gowane, Gopal; Alex, Rani; Mukherjee, Anupama; Verma, Archana; Deb, Sitangsu Mohan (Frontiers in Genetics, 2021)
Murrah breed of buffalo is excellent dairy germplasm known for its superior milk quality in terms of milk fat and solid not fat (SNF), however, it is often reported that Indian buffaloes had lower lactation and fertility potential compared to non-native cattle of the country. Recent techniques particularly the Genome-wide association studies to identify genomic variations associated with lactation and fertility traits offer prospects for systematic improvement of buffalo. DNA samples were sequenced using double digestion RAD tag genotyping-by-sequencing. Bioinformatics pipeline was standardized to call the variants and SNPs qualifying the stringent quality check measures were retained for GWAS. Over 38,000 SNPs were used to perform GWAS on the first two principal components of test day records of milk yields, fat percentages, and SNF percentages, separately. GWAS was also performed on 305 days milk yield, lactation persistency estimated through rate of decline after attaining the peak yield method, along with other three standard methods, and breeding efficiency, post-partum breeding interval, and age at sexual maturity were considered as fertility traits. Significant association of SNPs was observed for the first principal component explaining the maximum proportion of variation in milk yield. Further, some potential genomic regions were identified to have a potential role in regulating milk yield and fertility in Murrah. Identification of such genomic regions shall help in carrying out an early selection of high-yielding persistent Murrah buffaloes, and in the long run, would be helpful in shaping their future genetic improvement programs.